Supporting programmes of the growing of short rotation coppices in the Czech Republic - H. Součková (Agricultural Economics (AGRICECON), 2006)
This article presents some partial conclusions from the solution to the Research Project QF 4142 Higher exploitation of non-food production in the industry. The funding and supporting programmes of the growing of short rotation coppices (SRC) are described. The establishment of short rotation coppices and the subsequent exploitation of wood mass are promising trends of diversification of farmers' activities in the rural space. Plot sizes in ha and financial support to the establishment of the SRC plantations are given for 2001-2004, when a total of 166 ha of supported short rotation coppices was established. The establishment support is paid at a single installment while the amount paid for the establishment of the SRC production plantation is 60 000 CZK/ha and the amount paid for the establishment of mother plantation (reproduction plantation) is 75 000 CZK/ha.